Hubungan Pengetahuan dan Sikap Pasien dengan Upaya Pengendalian Hipertensi di Poliklinik Penyakit Dalam Rumah Sakit - Zikran; Mashudi; Fahrurazi; Fitriani, Sukmah (Jurnal Penelitian Multidisiplin Ilmu, 2024)
Introduction: Hypertension is abnormally high blood pressure and is often called the silent killer. In general, a person is considered to have hypertension if their blood pressure is higher than 140/90 mmHg. Efforts to control hypertension require patient knowledge and attitude. Objective: This study is to determine the relationship between knowledge and attitudes of patients with efforts to control hypertension in the internal medicine polyclinic of the Hospital. Methods: This study used an analytic survey method with a cross-sectional approach. The population in this study was 569 and the sample size was 64 respondents. Data obtained from respondents in this study using a research instrument in the form of a questionnaire. Results: Analysis of the relationship between patient knowledge and hypertension control efforts using the Chi Square test obtained a p-value = 0.001, which is p < 0.05 and analyzing the relationship between patient attitudes and hypertension control efforts using the Chi Square test obtained a p-value = 0.000, which is p < 0.05. Conclusion: There is a relationship between patient knowledge and attitude with hypertension control efforts. It is recommended for further research to conduct research on other factors that influence hypertension control efforts.